DIGITAL INNOVATION ECOSYSTEMS AS A MECHANISM FOR ECONOMIC DEVELOPMENT (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines digital innovation ecosystems as an important mechanism for economic development in the context of the growing digitalization of production, business, and social relations. The relevance of the topic is determined by the fact that in the modern economy, innovation is increasingly created not within isolated organizations, but through interaction among firms, technology platforms, research institutions, startups, investors, and public authorities. In such conditions, digital innovation ecosystems become a special environment that supports the generation, diffusion, and commercialization of new ideas, technologies, and digital solutions. Their role is especially significant because they contribute not only to technological progress, but also to structural economic transformation, productivity growth, and the strengthening of national competitiveness.The study is based on the understanding that digital innovation ecosystems function as interconnected networks in which digital infrastructure, data exchange, institutional support, and collaborative management create conditions for sustainable innovation activity. The article emphasizes that such ecosystems enhance economic development by accelerating knowledge transfer, reducing barriers to innovation, improving access to digital resources, and stimulating entrepreneurial activity. Particular attention is given to the interaction between technological, organizational, and institutional factors that determine the effectiveness of digital innovation ecosystems in various sectors of the economy.The research shows that digital innovation ecosystems can serve as an effective mechanism for economic development when they ensure coordination among key actors, support continuous innovation processes, and create favorable conditions for the emergence of new business models and digital markets. As a result, the article substantiates the importance of strengthening digital infrastructure, institutional cooperation, and innovation-oriented governance in order to improve the contribution of digital innovation ecosystems to long-term and sustainable economic growth.